Hubungan antara kepimpinan instruksional dan iklim sekolah di Sekolah Kebangsaan Zon Batu Anam Segamat - Mohamed, Nilam (2013)
This study aims to examine the relationship between teachers instructional leadership with school climate profile leads. This relationship is studied based on the perceptions of teachers on the frequency of their principals in performing the functions of instructional leadership and their perceptions of the determinants of the existence of the school climate that is conducive in their respective schools. The sample consists of 130 teachers from eight primary school at Zon Batu Anam, Segamat randomly selected. This study used questionnaires Principal Instructional Management Rating Scale and CFK Ltd. School Climate Profile. Data were analyzed using SPSS (Statistical Packages for the Social Sciences) version 18.00. Descriptive statistical methods used for the frequency, percentage, mean and standard deviation. Multivariate statistics are used to perform Pearson correlation test and one-way ANOVA. The results showed that the teachers frequently perform his functions as instructional leaders. Frequency only at a moderate level. Similarly, the profile of the school climate, teachers have a good perception of the existence of their school climate profile. The results also showed that there is a significant positive relationship between moderate to instructional leadership and school climate with r = 0.457.